Chosen problems of the aerodynamics of playing the wind instruments - PAWŁOWSKI, Zygmunt; ŻÓŁTOWSKI, Marek (Archives of Acoustics, 1985)
The authors modified the aerodynamic method for the diagnostics of the function of the respiratory organ during playing the wind instruments. The essence of this method is the possibility of measuring the value of the air pressure in the respiratory tracts without puncture into the trachea and obtaining the aerodynamogram curve. This curve permits the phenomena occurring during the play to be recorded, according to the division into three periods: 1) inspiration, 2) expiration until a given sound is formed, 3) the further duration of the expiration phase until its end. In the course of the investigations, it was found that the respiratory organ of the musician compensates automatically for the sudden increase of pressure in the lungs, which is necessary for the with given pitch and intensity to form. The air pressure distribution in the respiratory organ is nonuniform – the highest value occurs in the lung vesicles, the lowest one appears in the upper parts of the respiratory tracts.